Decomposing budget credibility - Felix Mambo; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Budget reliability is the first pillar of Public Expenditure and Financial Accountability (PEFA). In this study, we construct an expansion of the PEFA government response accuracy indicator and test its decomposition, with an application to the government budgets and state general accounts of Mozambique from 2014 to 2020. A special focus is given to public expenditure in social sectors: education, health, social protection, and public works. We find that the overall indicator of budget reliability hides significant differences in the budget credibility of different sectors, with social sectors contributing more to budget credibility than their weight in overall public expenditure. We find a strong suggestion that the budgeting and execution of public investment and-even more so-of externally financed public investment, is a weakening factor of budget credibility in Mozambique. Further, resources originally budgeted for investment seem to be possibly used to fund current expenditures. Finally, there is no strong evidence that midfiscal-year budget adjustments contribute to higher budget reliability. Our results suggest that the decomposition we propose adds valuable information that can support budget oversight and guide in-depth analyses of budget discrepancies.
Keywords: H61; H5; C65; 330; public finance management; PEFA; budget credibility; decomposition; social sectors